2017
DOI: 10.1021/jacs.7b06081
|View full text |Cite
|
Sign up to set email alerts
|

Oriented Films of Conjugated 2D Covalent Organic Frameworks as Photocathodes for Water Splitting

Abstract: Light-driven water electrolysis at a semiconductor surface is a promising way to generate hydrogen from sustainable energy sources, but its efficiency is limited by the performance of available photoabsorbers. Here we report the first time investigation of covalent organic frameworks (COFs) as a new class of photoelectrodes. The presented 2D-COF structure is assembled from aromatic amine-functionalized tetraphenylethylene and thiophene-based dialdehyde building blocks to form conjugated polyimine sheets, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
283
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 366 publications
(288 citation statements)
references
References 58 publications
2
283
0
3
Order By: Relevance
“…[46] The remarkable stability of BDT-ETTA in a wide range of pH aqueous solutions and strong absorption of visible light makes it a promising photoabsorber material. Bein and coworkers first explored COFs as photoelectrodes for such applications in the absence of both cocatalyst and sacrificial agent.…”
Section: Catalysismentioning
confidence: 99%
“…[46] The remarkable stability of BDT-ETTA in a wide range of pH aqueous solutions and strong absorption of visible light makes it a promising photoabsorber material. Bein and coworkers first explored COFs as photoelectrodes for such applications in the absence of both cocatalyst and sacrificial agent.…”
Section: Catalysismentioning
confidence: 99%
“…The first is solvothermal synthesis, in which the COF is grown directly on a solid support . This method produces highly crystalline films, with pores sometimes oriented perpendicular to the substrate, but suffers from numerous disadvantages, including difficult scale‐up, lack of generality across substrate types, production of powder products in addition to the film, and the inability to transfer films between supports . The second is interfacial polymerization, in which the monomers or catalyst are dissolved separately in two immiscible solvents such that COF formation occurs at the interface .…”
Section: Introductionmentioning
confidence: 99%
“…[3] Covalent organic frameworks (COFs), [6][7][8][9][10] crystallinep orousm aterials formed by the self-assembly of purely organic building blocks, have been explored for aw ide range of applications, such as optoelectronics, [11][12][13] gas storage, [14] and catalysis. [15][16][17][18][19][20][21][22] COFs have also shown promise as adsorbents for organic dyes, [23][24][25][26][27] mercury, [28,29] radionuclides, [30] and lanthanides, [31] as carriers for drug delivery, [32][33][34] and isolation of industriallyr elevant compounds. [35] Recently, we demonstrated that COFs can be used to efficientlyc apture marine toxin okadaic acid from seawater.…”
mentioning
confidence: 99%